POLITIK PERATURAN PERUNDANG-UNDANGAN TERHADAP PERLINDUNGAN HAK ASASI MANUSIA BAGI PEKERJA MIGRAN DI JAWA TIMUR - Rohi, Arvy Iedara (Jurnal HUKUM BISNIS, 2025)
Indonesian Migrant Workers (IMWs) continue to face numerous challenges at every stage of the migration process—before departure, during employment abroad, and upon returning to Indonesia. These challenges arise largely due to the lack of comprehensive government attention, especially in terms of effective protection mechanisms and policies. One major issue is the high number of non-procedural or undocumented migrant workers, which exposes them to various forms of exploitation and abuse. East Java Province, known as one of the regions with the highest number of migrant workers, bears a significant responsibility in ensuring the protection and fulfillment of the rights of its migrant workers. The provincial government must actively engage in implementing human rights-based policies and programs, ensuring that Indonesian Migrant Workers and their families are safeguarded from human trafficking, forced labor, slavery, violence, and any actions that degrade human dignity. Protection must be inclusive, covering all phases—from pre-departure training and documentation, to support systems while abroad, and reintegration programs upon return. Strengthening inter-agency coordination, increasing public awareness, and empowering migrant worker families at the village level are crucial steps toward sustainable protection and justice for migrant workers from East Java. Keywords: Indonesian Migrant Workers, Human Rights, Protection, East Java